Effective attributes of successful strategic information systems planning for public organizations in Middle East-preliminary study - Nezakati, Hossein; Harati, Ashkan; Elahi, Reihane (Asian Network for Scientific Information, 2014)
Rapid changes in information technology and business environment challenge the ability of organizations to undertake strategic planning for information systems and information technologies. Strategic information systems planning requires experienced human resources and growing heavy investments. Strategic information systems planning has turned into one of the top issues currently facing top management. Organizations are seeking ways to improve strategic information systems planning. This preliminary study was an attempt to identify effective attributes that may contribute to Strategic information systems planning success in state organizations in Middle East countries. The key attributes that may affect Strategic information systems planning success were identified by reviewing earlier research studies. Confirmatory factor analysis and fitness test were performed on the study conceptual model by applying constructive formulation modeling technique and using LISREL software and the results indicated fitness of the conceptual model. Identified attributes were grouped into three classifications: (1) General organizational attributes including change management and information systems maturity; (2) Interactive organizational attributes including top management participation and commitment and chief executive officer and chief information officer relationship and (3) Strategic information technology/information systems planning dimensions comprising of environmental assessment and strategic alignment. Three primary hypotheses and six secondary hypotheses of this preliminary Study will be examined the significance of the relationship between independent variables (effective attributes) and strategic information systems planning.